Auxiliary elements of mammalian pre-mRNAs polyadenylation signals - Zarudnaya, M.I.; Potyahaylo, A.L.; Kolomiets, I.M.; Hovorun, D.M. (Біополімери і клітина, 2002)
Polyadenylation is one of the levels at which eukaryotic gene expression is regulated. The auxiliary elements of mammalian polyadenylation (poly(A)) signals are known to influence positively or negatively the efficiency of 3'-end processing. In this paper, we surveyed the literature on auxiliary elements of mammalian poly(A) signals. We also compiled the database of human poly(A) signals and searched it for auxiliary elements. This database contains 244 pre-mRNA sequences covering the cleavage region. Literature data and our database screen demonstrated that auxiliary elements, particularly, sequences binding Ul snRNP-specific UJ A protein, are widely presented in cellular pre-mRNAs. Besides, we analyzed our database for the availability of the polynucleotide sequences with a potential to form G-quadruplexes or i-motifs which we consider as possible auxiliary elements. Based on published experimental findings on formation of quadruplexes, the schematic structures of possible quadruplexes are proposed for several human pre-mRNAs. The structures of putative quadruplexes are oho represented for G-rich auxiliary downstream element of SV40 L poly(A) signal